ZOOM MEET: ALTERNATIVE MEDIA FOR SUPPORTING ARABIC LANGUAGE LEARNING DURING THE PANDEMIC - Salam, Muhammad Yusuf; Mudinilllah, Adam (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2022)
This study aimed to explore the process of supporting Arabic learning using the Zoom Meet learning media. The research method used a descriptive qualitative approach. Research explains that Zoom Meet has excellent potential to support Arabic learning during the Covid-19 period. The research subjects were lecturers and students from the Arabic language education State Institute for Islamic Studies Batusangkar. There is documentary evidence from this research in the form of photo screenshots when using the Zoom Meet learning media; with this, it can be expected to find out how influential Zoom Meet is in learning Arabic courses. This study concluded that there are several responses regarding the classification, which will be negative and positive responses, which will describe the weaknesses and shortcomings of the Zoom Meet learning media. Through observations and interviews with lecturers and students of the Arabic language education study program, it is clear that the Zoom Meet media is an alternative media in supporting Arabic learning during the Covid-19.